LIMNOLOGY AND FISHERIES OF AN UPLAND RESERVOIR IN NILGIRIS - Palaniswamy, Rani; MURUGESAN, V K; MANOHARAN, S (Journal of the Inland Fisheries Society of India, 2016)
Sandynulla reservoir in Nilgiris was studied to understand the biotic and abiotic factors, primary production and the fishery. This reservoir was stocked with seed of Indian major carps (catla, rohu and mrigal) during seventies but sincethese fishes failed to establish in this reservoir, their stocking was discontinued. Instead, composite seed of C. carpio, H. molitrix, C. idella and L. fimbriatus were stocked @ 10 to 79 No./ha. Exploitation started from 1963-64 and 0.5 t offish was caught in the same year. The fish catch improved gradually and reached a peak (7.36 t) in 1968 - 69. Subsequently, the yield declined and fluctuated between 2.0 t and 6.6 t with an average of 4.23 t (16.0 kg/ha/yr).